Investigations on an All-Oxide Ceramic Composites Based on Al2O3 Fibres and Alumina–Zirconia Matrix for Application in Liquid Rocket Engines - Christian Bach; Frank Wehner; Jan Sieder-Katzmann (Aerospace, 2022)
High performance ceramics, particularly Ceramic Matrix Composite (CMC) materials found their way into liquid rocket engines. Yet, so far, mainly carbide or nonoxide CMCs have been of interest. This paper explores the potential and challenges of oxide–oxide ceramic matrix composites (OCMCs) for application in rocket thrust chambers. Therefore, strength, leakage and hot gas tests are conducted with material samples. A particular focus lies on the application of coatings to seal the permeability inherent to the material. Furthermore, prototypes in the form of flame tubes, ceramic chambers with nozzles and ceramic chambers with graphite inlays are developed and investigated experimentally in test firings. The results show that a recrystallised glass of a Y-Al-Si-O compound can successfully create an impermeable coating of the OCMC without affecting its damag-tolerant behaviour. However, the prototype developments show that it is still very challenging to manufacture even slightly complex structures without critical failures. Nevertheless, OCMC structures of relatively simple geometries showed promising results in hot firings and could be used as a lightweight housing, while the inner contour of the chamber and nozzle are realised, e.g., by a graphite inlay of appropriate quality.